Determination of total serum sulfite by HPLC with fluorescence detection - Ji, AJ; Savon, SR; Jacobsen, DW (Clinical chemistry (Baltimore, Md.), 1995)
An estimated 500,000 individuals in the US, mostly steroid-dependent asthmatics, suffer severe adverse reactions to sulfites in foods, beverages, and pharmaceutical products. In an attempt to understand the pathogenesis of sulfite hypersensitivity, we have developed an assay for the determination of total serum sulfite by utilizing: (a) reductive release of serum protein-bound sulfite; (b) derivatization of free sulfite with monobromobimane; (c) separation of sulfite-bimane from thiol-bimanes by reversed-phase HPLC; and (d) quantitation of sulfite-bimane by fluorescence detection. The detection limit of this assay was 0.44 mumol/L serum sulfite. The intra- and interassay CVs for total serum sulfite at 5.4 mumol/L were 8.1% and 22.0%, respectively. The standard addition method was used to determine total serum sulfite in normal subjects. More than 70 samples were prepared in 2-3 h, followed by automated overnight analysis. The mean concentrations (+/- SD) of total serum sulfite in female (n = 41) and male (n = 35) donors were 4.63 +/- 2.33 and 5.16 +/- 2.68 mumol/L, respectively (not statistically significant: P = 0.368). The combined mean concentration of total sulfite in both sexes was 4.87 +/- 2.49 mumol/L. There was no correlation between total serum sulfite and total serum cysteine, cysteinylglycine, homocysteine, subject age, serum cobalamin, or serum folic acid. The reference range (mean +/- 2 SD) for total serum sulfite in normal subjects is 0-9.85 mumol/L.